2008
DOI: 10.4319/lo.2008.53.6.2374
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution of zooplankton in subalpine and alpine lakes: Ultraviolet radiation, fish predation, and the transparency‐gradient hypothesis

Abstract: The transparency-gradient hypothesis argues that ultraviolet radiation (UV) is a primary determinant of the vertical distribution of zooplankton in transparent lakes with fewer fish, while fish predation is the primary driver in less transparent lakes where fish are more abundant. We measured vertical profiles of UV, photosynthetically active radiation (PAR, essentially visible light used as a proxy for fish predation), temperature, pH, conductivity, chlorophyll a (Chl a), and zooplankton in seven subalpine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 41 publications
(54 reference statements)
2
59
0
Order By: Relevance
“…For example, avoidance of depths with high UVR during daytime is an effective strategy that is particularly relevant to Daphnia species (Leech & Williamson, 2001), but it has also been observed in copepods (Alonso et al, 2004). In fact, in clear and fishless alpine lakes, UVR has been proposed to be the primary determinant explaining the vertical distribution of zooplankton (Kessler et al, 2008). However, avoidance may not be enough to obtain full protection in shallow ponds and lakes where, in addition, wind-driven mixing can recurrently bring planktonic organisms to the surface where UV irradiance levels are highest.…”
Section: Introductionmentioning
confidence: 97%
“…For example, avoidance of depths with high UVR during daytime is an effective strategy that is particularly relevant to Daphnia species (Leech & Williamson, 2001), but it has also been observed in copepods (Alonso et al, 2004). In fact, in clear and fishless alpine lakes, UVR has been proposed to be the primary determinant explaining the vertical distribution of zooplankton (Kessler et al, 2008). However, avoidance may not be enough to obtain full protection in shallow ponds and lakes where, in addition, wind-driven mixing can recurrently bring planktonic organisms to the surface where UV irradiance levels are highest.…”
Section: Introductionmentioning
confidence: 97%
“…Bags were randomly loaded into racks and incubated for 7 d at a depth of 7 m in Beauty Lake. This depth was selected because it was well below the depth to which damaging ultraviolet-B radiation penetrates in this lake (2.5 m) but still above the depth of 10% PAR (, 9 m; Kessler et al 2008), keeping it well within the photic zone. We confirmed these light conditions with the BIC prior to incubation.…”
Section: Methodsmentioning
confidence: 99%
“…The depth to which 1% of photosynthetically active radiation (PAR) remains (Z 1%PAR ) was previously measured for some of the lakes in July and August of multiple years (Kessler et al 2008;Rose et al 2009;Saros et al 2010). For those not previously measured, the Z 1%PAR was determined with a Biospherical Instruments Cosine (BIC) submersible profiling radiometer (Biospherical Instruments).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated pronounced differences in the behavioural responses of zooplankton to UV radiation. Copepods and rotifers exhibit a greater UV tolerance than cladocerans, which often show strong UV avoidance of surface waters (Leech and Williamson, 2000;Leech et al, 2005b;Kessler et al, 2008).…”
Section: Introductionmentioning
confidence: 99%